2021
DOI: 10.1002/admt.202101034
|View full text |Cite
|
Sign up to set email alerts
|

All‐3D‐Printed, Flexible, and Hybrid Wearable Bioelectronic Tactile Sensors Using Biocompatible Nanocomposites for Health Monitoring

Abstract: Physiological signals contain a wealth of personal health information which needs continuous monitoring for early detection of disease‐induced physiological irregularities and can be established as a potential approach to developing personalized healthcare devices. However, it is restricted by the lack of cost‐effective, precise, sensitive, and biocompatible flexible wearable sensors that are rapidly, reliably, and cost‐effectively are integratable. Here the work is reported on the development of novel, multim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 82 publications
(56 reference statements)
1
21
0
Order By: Relevance
“…Similar studies were reported elsewhere by Yi et al (2021), wherein they used an all-3D-printed, flexible, and wearable hybrid bioelectronic tactile sensor fabricated using biocompatible nanocomposites. They show comparable results to the previously discussed studies with advantages of low detection limits, quick response rates, excellent biocompatibility, better compressibility, and a matching modulus of elasticity with human skin [ 74 ]. Developments in strain and tactile sensors have a multitude of applications, like monitoring general physical health, social interactions, assistance to specially abled populations, improving athletic performance and rehabilitation, and measuring sleep quality, among other applications.…”
Section: Electromechanical Biosensorssupporting
confidence: 80%
“…Similar studies were reported elsewhere by Yi et al (2021), wherein they used an all-3D-printed, flexible, and wearable hybrid bioelectronic tactile sensor fabricated using biocompatible nanocomposites. They show comparable results to the previously discussed studies with advantages of low detection limits, quick response rates, excellent biocompatibility, better compressibility, and a matching modulus of elasticity with human skin [ 74 ]. Developments in strain and tactile sensors have a multitude of applications, like monitoring general physical health, social interactions, assistance to specially abled populations, improving athletic performance and rehabilitation, and measuring sleep quality, among other applications.…”
Section: Electromechanical Biosensorssupporting
confidence: 80%
“…The main limitations of the proposed model arise from the linearization of the electromechanical coupling (10). The DC offset of the driving voltage and the change in thickness of the actuator during dynamic excitation (the thickness of the dielectric influences the generated force (3)) cannot be represented by the defined (linear) transfer functions.…”
Section: Electromechanical Couplingmentioning
confidence: 99%
“…Fully 3D-printed dynamic sensors [5] introduced in recent years are capable of measuring acceleration [6,7], force [8,9], pressure [10,11], and strain [12,13]. Conductive polymer nanocomposites enable the imprinting of conductive networks [14,15] and passive electrical elements [16].…”
Section: Introductionmentioning
confidence: 99%
“…[14,17,18] The recent advancements in the development of different conducting inks (e.g., nano particles, nanotube compositions), and insulating inks (i.e., polydimethylsiloxane (PDMS), styrene-ethylene-butylene-styrene (SEBS)) in combination with rapid 3D-printing technology, have enabled us to manufacture various wearable sensing devices more rapidly and cost-effectively. [19] The proposed WB 2 F3D sensor system here consists of two modular units, 1) a disposable and noninvasive pH sensor, and 2) a reusable near-field communication (NFC)-based electronic/ communication circuitry and antenna, both together enable real-time, wireless, and battery-free in situ pH monitoring. The pH sensor is fabricated on a highly flexible SEBS substrate.…”
Section: Introductionmentioning
confidence: 99%